Comparative Study of Different Irrigation Protocols in Endodontic Treatment - Midhun Paul; Rekha V. Ravi; Chintu Sundaresan; Dinesh G. Kamath; Gargi Yumnam; Nada M. Ibrahim (Journal of Pharmacy and Bioallied Sciences)
Background: Irrigation is ideal in endodontic treatment as it helps in the removal of bacteria, softening of the organic structure, and then evacuation of debris in the root canal. Materials and Methods: This in vitro study involved 60 extracted single-rooted human teeth, randomly assigned to three groups (n = 20) based on the irrigation protocol used: The three tested products were Group A, sodium hypochlorite 5. 25%; Group B, Chlorhexidine 2%; and finally, Group C, EDTA 17%. Both groups rated equal in terms of the root canal preparation they were put through. A microbiological technique, debris, and smear layer removal were employed to determine irrigation efficacy, and scanning electron microscopy (SEM) was used on the extracted roots. In this study, the analysis of variance and post hoc tests were used with a predetermined alpha level of (0.05). Results: Comparing all the groups, Group A exhibited the best performance with Group B being the second best as seen with the mean log reduction of the bacterial load being 5. With 4.77 (±0. 54), Group A had the highest mean log reduction, while Group B recorded a mean log reduction of 2 (±0. 4). 54 (±0. 36) and Group C had a mean log reduction of 3. 9 (±0. 6). The SEM analysis for Group A was as follows: the cleanliness of samples was found to 85% in contrast to 70% in Group B and 50% in Group C (P < 0.05). Conclusion: Sodium hypochlorite 5. Twenty five percent was found to be the most effective Results showed that 25% is the most effective irrigation protocol in lowering bacterial count as well as in flushing out debris and smear layer from root canal.